ARTIFICIAL INTELLIGENCE AND 6G INTEGRATION: TRANSFORMING THE DIGITAL TECHNOLOGY LANDSCAPE - Rimsha Khan; Bibi Zainab; Abdullah Al Prince; Maria Iftikhar; Ali Raza (Spectrum of Engineering Sciences, 2025)
The combination of AI with 6G wireless networks is expected to transform the future digital era by facilitating novel advances in connectivity, automation, and intelligence. As research into 6G speeds up with the goal towards anticipated deployments around 2030, AI has become one of the cornerstones that move networks from static infrastructure into dynamic, self-optimizing ecosystems. This paper examines the synergistic opportunities between AI and 6G, including real-time data-processing, AI-native system architectures, and intelligent radio frequency beam forming, which could deliver terabits per seconds speeds, sub-millisecond latencies, and truly global coverage. Beyond such technical enhancements, the integration of AI and 6G will revolutionize industries such as healthcare, smart cities, autonomous transportation and immersive media by bridging the physical, digital and virtual worlds, for example through holographic communications, remote robotic surgery and the realization of real-time digital twins. But this evolution will not be without complications, from cybersecurity risks to expensive infrastructure and ethical quandaries around AI governance. Institution and media 5 pressures we believe that these may be addressed under a collaborative process that integrates efforts from academia, industry and policy makers, to ensure them and secure deployment. The merging of AI with the 6G would not just be an evolutionary development in wireless technology but also a paradigm shift to cognitive networks, which are able to make decisions by itself and learn from it. As global efforts struggle to define the contours of a 6G future, this paper calls for a balanced approach to innovation that prioritizes sustainability, inclusivity, and ethical frameworks to realize the untapped potential of intelligent connectivity. The age of AI-powered 6G does not just mean connecting the world more seamlessly, but redefining the very texture of digital interaction for decades to come. Keywords (6G networks, Artificial intelligence, Network optimization, Smart cities, Cybersecurity).